Great Illustrated Classics/ Pollyanna - Porter, Eleanor H. (Eleanor Hodgman), 1868-1920.; Leighton, Marian; Gual. (New York : Baronet Books, 1995)
When orphaned, eleven-year-old Pollyanna comes to live with austere and wealthy Aunt Polly, her philosophy of gladness brings happiness to her aunt and other unhappy members of the community.
Accelerated Reader AR
Keywords: Orphans -- Fiction; Aunts -- Fiction; Conduct of life -- Fiction; Fiction